Sero-prevalence of rubella among pregnant women in India, 2017. Issue 52 (18th December 2018) - Muliyil, Divya Elizabeth; Singh, Pratibha; Jois, Srinivas Krishna; Otiv, Suhas; Suri, Vanita; Varma, Vishakha; Abraham, Asha Mary; Raut, Chandrakant; Gupta, Minakshi; Singh, Mini P.; Viswanathan, Rajalakshmi; Naik, Sadanand; et al.
Highlights: Rubella IgG sero-prevalence among pregnant women in the six sentinel sites was found to be high. High sero-prevalence, in absence of immunization indicates continued transmission of rubella. Periodic sero-surveys among pregnant women could be useful to monitor rubella sero-prevalence. Abstract: Background: We conducted a sero-survey among pregnant women attending antenatal clinics of six hospitals which also function as sentinel sites for CRS surveillance, to estimate the prevalence of IgG antibodies against rubella. Methods: We systematically sampled 1800 pregnant women attending antenatal clinics and tested their sera for IgG antibodies against rubella. We classified sera as seropositive (titre ≥10 IU/ml), sero-negative (titre <8 IU/ml) or indeterminate (titre 8–9.9 IU/ml) per manufacturer's instructions. In a sub-sample, we estimated the titers of IgG antibodies against rubella. IgG titer of ≥10 IU/mL was considered protective. Results: Of 1800 sera tested, 1502 (83.4%) were seropositive and 24 (1.3%) were indeterminate and 274 (15.2%) were sero-negative. Rubella sero-positivity did not differ by age group, educational status or place of residence. Three hundred and eighty three (87.8%) of the 436 sera had IgG concentrations ≥10 IU/mL. Conclusion: The results of the serosurvey indicate high levels of rubella sero-positivity in pregnant women. High sero-prevalence in the absence of routine childhood immunization indicates continued transmission of rubella virus in cities where sentinel sites are located.